Hambatan Kematangan Perencanaan Karir Mahasiswa sebagai Generasi Millenial - Nurlela, Nurlela; Surtiyoni, Endang (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
The dilemma in determining career options is always faced by end-level students. Ironically as their millenials actually have a lot of options, but because of their no career planning cause they are hesitant in choosing a career option. Research aims to examine obstacles found both internally and externally. Methods of study using survey methods. The results of the survey showed that internally confidence and low selfunderstanding became the main obstacle, while external expectations and adaptation to the lifestyle that makes students feel hesitant in determining career options. The study recommends the need for a career guidance student who focuses on the deepening of personality skills and typologies, in addition to students having to be used to perform creative projects in the PBL, and courses need to add a portion of field practice experience.